2022
DOI: 10.3389/fnut.2022.932670
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Branched-Chain Amino Acids and Branched-Chain α-Keto Acid Dehydrogenase Kinase in Metabolic Disorders

Abstract: Branched-chain amino acids (BCAAs), composed of leucine, isoleucine, and valine, are important essential amino acids in human physiology. Decades of studies have revealed their roles in protein synthesis, regulating neurotransmitter synthesis, and the mechanistic target of rapamycin (mTOR). BCAAs are found to be related to many metabolic disorders, such as insulin resistance, obesity, and heart failure. Also, many diseases are related to the alteration of the BCAA catabolism enzyme branched-chain α-keto acid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 81 publications
2
24
0
Order By: Relevance
“…Our data also demonstrated the alterations in the metabolism of branched-chain amino acids (BCAAs). BCAAs include valine, leucine, and isoleucine which are essential for organisms 42, 43 . It has been shown that BCAAs activate T cell types via mTOR signaling and glucose metabolism 44, 45, 46 .…”
Section: Resultsmentioning
confidence: 99%
“…Our data also demonstrated the alterations in the metabolism of branched-chain amino acids (BCAAs). BCAAs include valine, leucine, and isoleucine which are essential for organisms 42, 43 . It has been shown that BCAAs activate T cell types via mTOR signaling and glucose metabolism 44, 45, 46 .…”
Section: Resultsmentioning
confidence: 99%
“…Branched-chain amino acids (BCAAs) leucine, isoleucine, and valine are all essential AAs that can only be synthesized by bacteria, plants, and fungi, and also can be acquired from dietary chicken breast, beef, tuna, beans, and cherries. In contrast to the majority of AAs, BCAAs are converted to their branched-chain α-keto acids (BCKAs) in skeletal muscle and then released into systemic circulation [ 72 ]. BCAAs are well known for their crucial role in promotion of muscle-protein synthesis and modulation of energy metabolism during exercise, which are both mediated through activation of the mTOR signaling pathway [ 73 ].…”
Section: Branched-chain Amino Acidsmentioning
confidence: 99%
“…Consistent with protein-host interactions whose consequences lie in mitochondrial dysfunctions, the SARS-CoV-2 nsp12 protein has been suggested to inhibit branched-chain keto acid dehydrogenase kinase (BCKDK), a branched-chain amino acid kinase regulatory enzyme [26,43]. Interestingly, the accumulation of branchedchain amino acids, which in turn can inhibit pyruvate dehydrogenase, mitochondrial respiration chain and α-ketoglutarate dehydrogenase, can cause apoptosis in glial cells and neurons [44]. In addition, the nsp7 and nsp8 proteins have been described as two cofactors of the nsp12 protein, and both interact with ribosomal proteins in mitochondria [43].…”
Section: Cytopathic Effects On Mitochondriamentioning
confidence: 99%